Poverty Alleviation & Human Development: Comparative Analysis of Facebook pages of top three political parties of Pakistan during 2018 Election Campaign. - Siddique, Hassan; Farooqi, Umer; Ali, Muhammad (Journal of Peace, Development and Communication, 2020)
Every fourth Pakistani lives below the poverty line and it has been one of the most pressing issues across the world, especially in a developing country like Pakistan. First democratically elected Prime Minister of Pakistan won elections on a popular slogan (Food, cloth and shelter). Social Media in general and Facebook in particular has become a powerful influencing agent in Pakistan. According to AlphaPro (2018), there are more than 3.5 million active Facebook users, and 92 percent of internet users in Pakistan use Facebook. Therefore, this research focuses on the coverage of poverty alleviation on Facebook pages of top three political parties of Pakistan i.e. Pakistan Muslim League (Nawaz), Pakistan Tehreek-e-Insaf and Pakistan People’s Party. This research employs quantitative content analysis to determine the importance given to poverty alleviation and human development by Pakistani political parties on their Facebook pages. Results concluded that poverty alleviation or human development has not been the priority of top three political parties of Pakistan, but if we compare the selected three political parties, PTI took lead in discussing the poverty alleviation and human development on their official Facebook page during 2018 election campaign, whereas PMLN was neck to neck with PTI. On the contrary, PPP gave least priority to poverty alleviation or human development. Key Words: Poverty Alleviation, Facebook, Elections 2018, Human Development, Media ecology